ANALISIS KUALITAS BUTIR SOAL ASESMEN FORMATIF PADA PEMBELAJARAN BAHASA INDONESIA DI SMP - Fitria Anggraini D; Tatu Hilaliyah (Universitas Batanghari, 2026)
This study aims to analyze the quality of formative assessment questions in Indonesian language learning in Junior High School. Formative assessments play an important role in monitoring student learning progress and providing feedback for improving the learning process. However, the assessment instruments used need to meet quality criteria so that the assessment results obtained truly reflect students' abilities. This study uses a quantitative approach with a descriptive method. The research subjects were junior high school students who took part in the Indonesian formative assessment, while the research object was in the form of formative assessment questions in the form of multiple choice. Data was obtained from the results of the work on the questions by the students and analyzed using question item analysis techniques which included validity, reliability, difficulty, and differentiating power. The results of the study showed that the quality of formative assessment questions varied. Most of the question items have good validity and reliability, while some other items need to be revised or replaced. The level of difficulty of the questions is in the categories of easy, medium, and difficult proportionally, while the differentiating power shows the ability of the questions to distinguish between high and low ability students. Based on these results, it can be concluded that the analysis of question items needs to be carried out on an ongoing basis so that formative assessments can be used optimally in supporting Indonesian learning in junior high school.